ANALYSIS OF DEMOGRAPHIC AND EMPLOYMENT IMPACT ON ECONOMIC GROWTH IN INDONESIA - Aura Ulfha; Roswita Afni (Proceeding International Seminar of Islamic Studies, 2022)
Population growth is a major problem being faced by developing countries like Indonesia. The population problem is one of the problems faced by almost all developing countries in the world, especially due to high birth rates. High population growth has an impact on various aspects of life. This study aims to analyze the impact of demography and workforce on economic growth in Indonesia in 2016-2020. The variables in this study consist of Fertility, Mortality, Labor and Economic Growth. The data used in this study is panel data and uses E-views 12 software to analyze data using multiple linear regression. The results of this study indicate that fertility (birth) and labor have a significant and positive effect on Indonesia's economic growth, while other demographics. Mortality (death) is not significant and negative on economic growth in Indonesia